Nuts and bolts of the behavioural manipulation by Toxoplasma gondii - Vyas, Ajai (Folia parasitologica, 2024)
In this review, I take the first-person perspective of a neuroscientist interested in Toxoplasma gondii (Nicolle et Manceaux, 1908). I reflect on the value of behavioural manipulation as a perturbation tool to understand the organisation of behaviour within the brain. Toxoplasma gondii infection reduces the aversion of rats to the olfactory cues of cat presence. This change in behaviour is one of the often-discussed exemplars of host-parasite coevolution, culminating in the manipulation of the host behaviour for the benefit of the parasite. Such coevolution also means that we can use host-parasite systems as tools to derive fundamental insights about the host brain itself.
Keywords: Behavior, Animal; Toxoplasma; Parasite; Host-Parasite Interactions; interakce hostitele a parazita; Life-history; Fear; toxoplazmóza; krysa rodu Rattus; Toxoplasmosis, Animal; Animals; lidé; Toxoplasmosis; Humans; zvířata; Rats; chování zvířat; Amygdala; toxoplazmóza zvířat